Advanced Maternal Age, Mode of Delivery, and Thyroid Hormone Levels in Chinese Newborns - Fan, Pianpian; Luo, Zhong-Cheng; Tang, Ning; Wang, Weiye; Liu, Zhiwei; Zhang, Jun; Ouyang, Fengxiu (Frontiers in Endocrinology, 2020)
Objective: Thyroid hormones are essential for fetal growth and neurodevelopment, however, data on cord blood thyroid hormones are sparse in China where maternal age at childbearing is increasing in recent decades. We aimed to assess cord blood levels of free triiodothyronine (FT3), free thyroxine (FT4) and thyroid stimulating hormone (TSH) in full-term Chinese newborns, and examine potential related perinatal factors. Methods: This study included 922 mother-newborn pairs from a prospective birth cohort enrolled in 2012-2013, Shanghai, China. Cord serum concentrations of FT3, FT4, TSH, and TPOAb were measured in newborns. Results: Newborns born via cesarean section had higher cord serum FT3 (mean±SD: 1.90±1.16 pmol/L) and lower cord serum TSH (5.15±2.60 mIU/L) than those born via vaginal delivery (FT3: 1.62±0.93 pmol/L; TSH: 9.27±6.76 mIU/L). In cesarean section deliveries, the concentration of cord serum FT3 was 0.15 (95%CI: -0.03, 0.33; p=0.10) pmol/L lower in infants of mothers aged 30-34 years, and 0.57 (95%CI: 0.22, 0.92; p=0.002) pmol/L lower in infants of mothers ≥35 years compared to infants of mothers <30 years. Large-for-gestational-age (birth weight >90th percentile) was associated with higher TSH (p=0.02). Similar results were also found in vaginal deliveries. Conclusions: In this Chinese term birth cohort, newborns born via cesarean section had higher cord serum FT3 and lower TSH than those born via vaginal delivery. Advanced maternal age was associated with lower fetal FT3. Further research is needed to understand whether this association may mediate the adverse impact of advanced maternal age on neurodevelopment in early life.